Toxicological safety evaluation in acute and 28-day studies of aqueous extract from Serjania marginata Casar. (Sapindaceae) leaves in rats - da Silva Moreira, Suyane [UNESP]; Tamashiro, Leticia Kaory [UNESP]; Jorge, Bárbara Campos [UNESP]; da Silva Balin, Paola [UNESP]; Heredia-Vieira, Silvia Cristina; de Almeida, Gabriela Lessa; Cardoso, Claudia Andrea Lima; Kassuya, Cândida Aparecida Leite; Arena, Arielle Cristina [UNESP] (Elsevier, 2019)
Ethnopharmacological relevance: Serjania marginata Casar. (Sapindaceae) is a species traditionally known to be used for the treatment of gastric pain and inflammatory symptoms. Aim of this study: Due to the therapeutic importance of this species, this study investigated the toxicological effects of S. marginata leaves (AESM), after a single and a repeated exposure in rats. Materials and Methods: For the acute toxicity test, 2000 mg/kg of AESM was administered to male and female rats by gavage, whereas for subacute toxicity test, 30, 150, or 750 mg/kg of AESM were used. Results: No evidence of toxicity was observed in the animals acutely exposed to the extract, indicating that the LD50 is higher than 2000 mg/kg. After the repeated administration of AESM the hematological and biochemical parameters were unaltered, except the erythrocytes number and albumin levels in the exposed animals. Moreover, daily administration of this extract caused alteration on kidney histology. AESM also induced an increase of abnormal sperm, however the other reproductive parameters analyzed, in both sexes, were not altered by the treatment. Conclusion: Although AESM was not toxic after a single exposure, its use after prolonged periods affected some analyzed parameters, indicating that precautions should be taken when it is given over longer periods.
Keywords: Acute toxicity; Reproductive parameters; Serjania marginata; Subacute toxicity